New Developments in Exosomal lncRNAs in Cardiovascular Diseases - Yuan, Zhu; Huang, Weiqiang (Frontiers in Cardiovascular Medicine, 2021)
Long non-coding RNAs (lncRNAs) are non-coding RNAs with lengths >200 nt and are involved in the occurrence and development of cardiovascular diseases (CVDs). Exosomes are secreted and produced by various cell types. Exosome contents include various ncRNAs, proteins and lipids. Exosomes are also important mediators of intercellular communication. The proportion of lncRNAs in exosomes is low, but increasing evidence suggests that exosomal lncRNAs play important roles in CVDs. We focused on research progress in exosomal lncRNAs in atherosclerosis, myocardial infarction, myocardial ischemia-reperfusion injury, cardiac angiogenesis, cardiac aging, rheumatic heart disease, and chronic kidney disease combined with CVD. The potential diagnostic and therapeutic effects of exosomal lncRNAs in CVDs are summarized based on preclinical studies involving animal and cell models and circulating exosomes in clinical patients. Finally, the challenges and possible prospects of exosomes and exosomal lncRNAs in clinical applications related to CVD are discussed.